Transitions from Infinite to Finite Games as Critical Moments. Issue 2 (25th March 2020) - Donohue, William A.
Abstract : This theory article argues that negotiation is often played as a finite game that consists of a known number of players using an agreed‐upon set of rules (when parties are bargaining in good faith) aimed at achieving a specific outcome. However, activities and events leading up to negotiation can be viewed as an infinite game that has no fixed entities such as personnel, rules, and outcomes. Thus, a critical moment occurs when parties agree to make the transition from some infinite game, like conflict, to the finite game of negotiation. This article explores the conditions leading up to this critical transition and provides two examples of negotiations—one that successfully made the transition and one in which the transition did not occur—to illustrate how these conditions function in actual contexts.